Drought stress induces salicylic acid accumulation, altering monoterpene profile and suppressing resin duct formation in Engelmann spruce - Thomas Seth Davis; Ehsan Khedive; Edward Hill; Troy Ocheltree (PLoS ONE, 2026)
Drought is a critical stressor on plants and often precedes large-scale insect outbreaks in forest ecosystems. Whether plant physiological mechanisms underlie this pattern remains uncertain; environmental conditions affect the growth rate of insect populations but also have consequences for plant defense phenotypes. To investigate the latter, we experimentally applied water stress to test relationships between drought, salicylic acid (SA) accumulation, and tree resistance factors including secondary metabolite (monoterpene) concentrations and formation of traumatic resin ducts in Engelmann spruce ( Picea engelmannii ), a widespread forest tree in western North America. Three key findings emerged. First, both acute and chronic water stress reduced stem water potentials, with evidence for loss of photosynthetic function as water potentials declined below −2.0 MPa. Negative water potential was associated with an increase in the concentrations of SA in both needles and stem phloem, but this trend was stronger in needles. Second, under water stress elevated SA concentrations were associated with increased concentrations of several structurally similar monoterpenes in needles and stem phloem, including β-phellandrene, δ-3-carene, γ-terpinene, and terpinolene. These trends were stronger in stem phloem than in needles. Lastly, chronic water stress inhibited the ability of P. engelmannii to form traumatic resin ducts in response to methyl jasmonate, a ubiquitous elicitor of inducible plant defenses. Collectively, our experiments show endogenous upregulation of SA in response to water stress in Engelmann spruce, resulting in changes to composition of volatile profiles and potentially suppressing induction of defense systems. These phenotypic changes may affect the performance of phloeophagous forest insects by altering plant resistance traits associated with defensive competency in response to herbivory.